Neuroprotective and axonal outgrowth-promoting effects of tetramethylpyrazine nitrone in chronic cerebral hypoperfusion rats and primary hippocampal neurons exposed to hypoxia. (15th May 2017) - Zhang, Tao; Gu, Jianbo; Wu, Liangmiao; Li, Ning; Sun, Yewei; Yu, Pei; Wang, Yuqiang; Zhang, Gaoxiao; Zhang, Zaijun
Abstract: Chronic cerebral hypoperfusion is an important risk factor for vascular dementia and other brain dysfunctions, for which there are currently no effective medications available. We investigated the neuroprotective and axonal outgrowth promoting effects of tetramethylpyrazine nitrone (TBN) in a permanent bilateral occlusion of the common carotid arteries (2VO) rat model and in primary hippocampal neurons exposed to oxygen glucose deprivation (OGD). At 6th week after 2VO, TBN increased the time spent in novel arms in the Y-maze test and improved the discrimination ratio in object reorganization task. TBN attenuated axonal damage, and reduced oxidative DNA injury and lipid peroxidation in white matter. TBN also attenuated the neuronal apoptosis and ameliorated accumulation of astrocytes in parietal cortex and CA1 region of hippocampus. Western blot analyses indicated that TBN increased Bcl-2 expression, decreased Bax and Caspase 3 expressions, and upregulated the phosphorylation levels of high-molecular weight neurofilament (p-NFH), Akt (p-Akt) and glycogen synthase kinase-3β (p-GSK3β) in hippocampus at 6th week after chronic hypoperfusion. In vitro, TBN rescued hippocampal neuronal viability and axonal elongation from OGD damage. The p-Akt and p-GSK3β upregulation by TBN was abolished by a specific phosphoinositide 3-kinase (PI3K) inhibitor LY294002, resulting in suppression of axonal outgrowth. Collectively, the results showed that TBN alleviated white matter lesion and impairment of cortex and hippocampus, attenuated oxidative damage and enhanced axonal outgrowth through the regulation of PI3K/Akt/GSK3β signaling pathway, leading to improved cognitive deficit in a rat chronic hypoperfusion model. Graphical abstract: Highlights: TBN improves learning memory deficits in 2VO rats. TBN ameliorates white matter injury and neurons loss in 2VO rats. TBN promotes axonal outgrowth in 2VO rats and in primary hippocampal neurons. TBN protects primary hippocampal neurons against OGD. TBN functions via activating PI3K/AKT/GSK3β and concurrently combating oxidative stress.